Back to the Cartesian: Pilot Study for Assessing Human Stiffness in 3D Cartesian Space by Transforming from Muscle Space in a Peg-In-Hole Scenario for Tele-Impedance - Thürauf, Sabine; Mehrkens, Florian; Castellini, Claudio; Sierotowicz, Marek (Proceedings - IEEE International Conference on Robotics and Automation, 2025)
For various teleoperation tasks, position-based control is not practical. An impedance-based control is superior e.g. for handling fragile objects, like harvesting fruits or grasping a paper cup. However, only a few researchers have focused on impedance control for teleoperation. In tele-impedance, the stiffness of a human is measured and transferred to a controller of a robot. Until now, human stiffness was mostly measured either for specific joints or in 2D Cartesian space. We introduce a new way of measuring Cartesian stiffness in 3D using electromyography. Users were asked to perform a peg-in-hole task in three different orientations (0°, 45°, 90°). Meanwhile, electromyography measurements at shoulder and elbow muscle groups are performed. In a proof-of-concept study, we showed that the measured stiffness matrix in Cartesian space differed significantly across the three differently oriented peg-in-hole scenarios. This demonstrates that human stiffness could be predicted in 3D Cartesian space based on the type of task at hand.
CRIS-Team Scopus Importer:2025-10-03